Faktor - Faktor yang Berhubungan dengan Tindakan Persalinan Sectio Caesarea (SC) di Rsud Banyuasin Tahun 2024 - Lusmiana; Putu Lusita Nati Indriani; Sendy Pratiwi Rahmadhani (Bulletin of Community Engagement, 2024)
Sectio Caesarea is a surgical procedure to deliver a fetus by making an incision in the abdominal wall and uterus of the mother. In several countries such as the Dominican Republic, Brazil, Free, Egypt and Turkey, caesarean sections are more common than normal births. This study aims to determine the factors associated with caesarean section delivery at Banyuasin Regional Hospital in 2024. This study uses an analytical survey approach with a Cross Sectional design. The population in this study were all mothers giving birth at Banyuasin Regional Hospital, totaling 217 mothers. The sample in this study was 68 respondents using a simple random sampling technique. The type of data used secondary data and the research instrument used the medical records of mothers giving birth. Data analysis used univariate and bivariate analysis with the chi-square statistical test. The results of the univariate analysis showed that out of 68 respondents who gave birth by section, 43 (63.2%). The results of the bivariate analysis are known using the Chi-square test that there is a significant relationship between the history of cesarean section (p Value = 0.0009), premature rupture of membranes (p value = 0.007) and there is no significant relationship between fetal abnormality with cesarean section delivery (p Value = 0.100). The conclusion is that there is a relationship between the history of cesarean section and premature rupture of membranes (PROM) with cesarean section delivery but there is no relationship between fetal abnormality with cesarean section delivery at Banyuasin Hospital. This study is expected to add references and literature for students and can provide information to the public about cesarean section delivery.